Swarm Intelligence Introduction and Applications - Blum, Christian; Merkle, Daniel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
The laws that govern the collective behavior of social insects, flocks of birds, or fish schools continue to mesmerize researchers. While individuals are rather unsophisticated, in cooperation they can solve complex tasks, a prime example being the ability of ant colonies to find shortest paths between their nests and food sources. Task-solving results from self-organization, which often evolves from simple means of communication, either directly or indirectly via changing the environment, the latter referred to as stigmergy. Scientists have applied these principles in new approaches, for example to optimization and the control of robots. Characteristics of the resulting systems include robustness and flexibility. This field of research is now referred to as swarm intelligence. The contributing authors are among the top researchers in their domain. The book is intended to provide an overview of swarm intelligence to novices, and to offer researchers in the field an update on interesting recent developments. Introductory chapters deal with the biological foundations, optimization, swarm robotics, and applications in new-generation telecommunication networks, while the second part contains chapters on more specific topics of swarm intelligence research such as the evolution of robot behavior, the use of particle swarms for dynamic optimization, and organic computing.
Biological Foundations of Swarm Intelligence -- Swarm Intelligence in Optimization -- Swarm Robotics -- Routing Protocols for Next-Generation Networks Inspired by Collective Behaviors of Insect Societies: An Overview -- Applications -- Evolution, Self-organization and Swarm Robotics -- Particle Swarms for Dynamic Optimization Problems -- An Agent-Based Approach to Self-organized Production -- Organic Computing and Swarm Intelligence.
Keywords: Computer science; Computers; Artificial intelligence; Computer simulation; Operations research; Management science; Control engineering; Robotics; Mechatronics; Electrical engineering; Computer Science; Artificial Intelligence (incl. Robotics).; Computation by Abstract Devices; Simulation and Modeling; Operations Research, Management Science; Control, Robotics, Mechatronics; Communications Engineering, Networks; Electronic books